Development of a graphene based immuno-biosensor for hepatitis b virus surface antigen detection - Geraldine Chan, Sue Ching (2016)
Hepatitis B virus (HBV) is a blood-borne and transfusion-transmitted human pathogen that has a large impact on blood safety and public health worldwide whereas reduced graphene oxide (RGO) is a derivatives of graphene which has gain much attention in electrochemical immunosensors. HBV infects the liver and causes chronic and acute Hepatitis. The best treatment for this disease is for the early detection before the occurrence of severe liver damages. The presence of Hepatitis B surface antigen (HBsAg) is evidence of presence of HBV infections. Presently, the conventional methods shows weakness in terms of time and efficiency. In this research, it aims to immobilize the HBsAg antibody (HBsAb) onto functionalized RGO as well as to study the interaction between HBsAb and HBsAg by electrochemical probe of the functionalized RGO. RGO was synthesized via modified Hummer’s methods and reduced using hydrazine hydrate. RGO is functionalized with nafion and thionine prior to immobilization of HBsAb. Qualitative analysis of functionalized RGO was conducted via ultraviolet-visible spectrophotometry (UV-Vis), fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and field emission scanning electron microscopy (FESEM). Electrochemical analysis of functionalized RGO probe electrode on the detection of HBsAg was done via cyclic voltammetry (CV). As a conclusion, successful immobilization of HBsAg on functionalized RGO was proven to obey Freundlich adsorption isotherm with maximum adsorption capacity of 31 ng HBsAg/g and further confirmed with the change in surface structure observed as well as the presents of functional groups detected. Interaction between HBsAg and HBsAb causes the colour change when tetramethylbenzidine (TMB) was added and step changes to occur during CV with a limit of detection at 0.5 ng/mL.